PRACTICE OF CONSIGNMENT SERVICES IN ONLINE TRANSACTIONS: FIQH MUAMALAH ANALYSIS OF THE AGREEMENT AND ITS MECHANISM - Iis Sukaesih; Mifathul Ulum; M. Salman Alfarizi; Erik Setiawan; Muhamad Ibnu Malik (ANAYASA : Journal of Legal Studies, 2026)
The rapid growth of digital commerce has encouraged the emergence of personal shopper services (jastip) as a form of online transaction involving third-party intermediaries. This phenomenon raises questions regarding the validity of contracts and transaction mechanisms from the perspective of Islamic jurisprudence (fiqh muamalah). This article aims to analyze the practice of online jastip by examining the types of contracts applied and their conformity with fiqh muamalah principles. The study employs a qualitative approach through library research, analyzing classical and contemporary fiqh literature, journal articles, and relevant fatwas concerning digital transactions. The findings reveal that the jastip practice predominantly applies the wakalah bil ujrah contract, in which consumers authorize service providers to purchase goods on their behalf in exchange for a service fee. This practice is considered permissible under Islamic law provided that the essential elements of the contract such as clarity of parties, object, consent, and remuneration are fulfilled. However, the study also finds that lack of transparency and unclear contractual terms may lead to gharar, affecting the validity of the transaction. Therefore, it is concluded that the permissibility of online jastip depends not on its digital form, but on the fulfillment of fiqh muamalah principles in its contractual mechanism.